Job satisfaction and symptoms of depression, anxiety, stress, and burnout: A survey of Australian and New Zealand intensive care research coordinators. Issue 1 (January 2023) - Yarad, Elizabeth; Bates, Samantha; Butler, Magdalena; Byrne, Kathleen; Eastwood, Glenn; Grattan, Sarah; Miller, Jennene; Morrison, Lynette; Murray, Lauren; Palermo, Annamaria; Sherring, Claire; Soar, Natalie; et al.
Abstract: Introduction: Intensive care unit clinical research is often implemented by specialised research coordinators (RCs). Clinical research activity within Australian and New Zealand intensive care units has escalated, particularly during the COVID-19 pandemic. Growth of the intensive care RC workforce to match research demand is poorly understood. Aim: The aim of this study was to repeat an Intensive Care Research Coordinator Interest Group workforce survey conducted in 2004 and 2009 to describe the current workforce and role satisfaction and also to determine reported symptoms of depression, anxiety, stress, and burnout in Australian and New Zealand intensive care RCs. Methods: In April 2021, an online anonymised survey was distributed to intensive care RCs to complete demographic and workforce questions, the McCloskey/Mueller Satisfaction Scale, the Depression Anxiety Stress Scales-21, and the Maslach Burnout Inventory–Human Services Survey for Medical Personnel. Results: Of 128 Intensive Care Research Coordinator Interest Group eligible members, 98 (77%) completed the survey. Respondents were mainly women (91%), the median age was 47 years, 37% have a postgraduate qualification, and a third have over 10 years of RCC experience (31%). Half do not have permanent employment (52%). The mean Depression Anxiety Stress Scales-21 scores were within the normal range, and respondents reported symptoms of depression (21 [21%]), anxiety (23 [23%]), and stress (26 [27%]). Nearly half of the respondents (44%) exhibited an early symptom of burnout by reporting problematic experiences of work. The overall role satisfaction score was 3.5/5 (neutral; neither satisfied nor dissatisfied). Conclusions: Intensive care RCs are an experienced group of professionals with limited satisfaction in the role. One-fifth of the ICU RCs experienced depression, anxiety, or stress symptoms, with close to half reporting signs of burnout. These results highlight the need to address areas of concern to ensure retention of this specialised intensive care workforce.